Melanoma with unknown primary presenting as pleomorphic malignancy– Role of Immunohistochemistry in the diagnosis - Sandip Dukare; Rajesh Thakur; Vikas Narhire; Shweta Ranka; Priya Deshpande (Asian Pacific Journal of Health Sciences, 2014)
Melanoma with unknown primary (MUP) accounts for approximately 1% to 8% of all melanomas and was described first in 1952. We report a case of a 95 year old male with a painless, progressively increasing swelling of the inguinal region, which on investigations came out to be malignant melanoma metastatic to inguinal nodes, without clinical or radiological evidence of a known primary. Metastatic melanoma is often confused with a variety of poorly differentiated carcinomas, sarcomas, and large cell lymphomas. Immunohistochemistry along with histopathology is important in the diagnosis and sub-classification of tumors. The importance of presenting this paper is to highlight the rare presence of malignant melanoma metastatic to lymph nodes with an unknown primary, and the role of immunohistochemistry in the diagnosis.